RUSSIA'S VIOLATION OF THE PRINCIPLE OF NON-INTERVENTION AGAINST UKRAINE IN THE PERSPECTIVE OF INTERNATIONAL LAW - Deni Yusup Permana (HERMENEUTIKA : Jurnal Ilmu Hukum, 2022)
Russia's participation in the internal affairs of Ukraine is something that should not be done. Because, it can violate the provisions of the United Nations Charter. Currently the security of countries is something that should be guarded. The behavior of the Russian state in violation of the principle of non-intervention by interfering in the independence of Donetsk and Luhansk which is part of the Ukrainian state. Russia's behavior has disturbed the Ukrainian household, which is actually what is happening in Ukraine is Ukrainian business because Ukraine is the one who knows better about the problems in his country. The purpose of this paper is to find out the violations of the principle of non-intervention that have been carried out by Russia against Ukraine and the responsibility of the Russian state for violations of the principle of non-intervention in the conflicts that occur within the Russian state. This writing uses normative legal methods or legal research which is a document study, such as by using laws and regulations, decisions or decisions from courts, contracts or agreements or contracts, legal theory.